Emotional Intelligence and Collaborative Work in High School Students: Theoretical Analysis - Luis Carmelo Fuertes MEZA; Johnny FÃ©lix FarfÃ¡n PIMENTEL; Janet Meluzka GarcÃa RIVEROS; Amparo Rosa Montellanos SOLIS (International Journal of Environmental, Sustainability, and Social Science, 2021)
The purpose of this article is to analyze the influence of emotional intelligence on collaborative work in high school students. The teaching-learning processes that are generated in the student in a given educational context, through cooperative work and the collaboration of the entire educational community generate an improvement in student learning in a quality and comprehensive education. In this way, working cooperatively with our students should be valued in the educational community to achieve the goals of the competencies foreseen in our educational system. At present it is relevant to find strategies for the change of an active methodology making use of our emotional intelligence using emotions as the main axis in addition to teamwork in order to solve challenging situations proposed by the teacher or problematic situations of their context. We will also learn about the four pillars of emotional intelligence, such as knowledge, aptitude, depth and emotional alchemy, which are related to understanding our emotions, self-regulation, empathy for others and social skills. Finally, significant contributions are made on emotional intelligence and collaborative work.